The New Testament and rabbinic literature - Bieringer, R. (Supplements to the Journal for the Study of Judaism, 2010)
The present book brings together the contributions of the foremost specialists on the relationship of the New Testament and Rabbinic Literature. It contains the proceedings of a Symposium held at the K.U.Leuven in January 2006. The contributors, from different European countries as well as from Israel, present in detail the history of rabbinical scholarship by Christian scholars and deal with the main issues in the study of rabbinic materials. As could be expected, much attention is given to halakhic issues, but literary questions in Midrash, Targum and Mystical Literature are also dealt with. All contributions are in English, and the volume is completed with a very large "cumulative bibliography" which will enhance its usefulness.